Maintaining Printing Machines at a Textile Company: Pemeliharaan Mesin Cetak di Perusahaan Tekstil - Rahmananto, Satrio Fajar; Tjahjanti, Prantasi Harmi (Universitas Muhammadiyah Sidoarjo, 2024)
This qualitative research explores the multifaceted applications of Polyvinyl Chloride (PVC) in East Java, Indonesia. Utilizing interviews, observations, and literature review, the study aims to analyze PVC's utilization across diverse sectors. Results highlight its extensive use in synthetic leather, flooring, and color manufacturing, emphasizing its versatility, chemical resistance, lightweight, and water-resistant properties. Implications underscore the importance of comprehending PVC's role for sustainable development and innovation. Highlight : PVC's Versatility: The study showcases PVC's adaptability across various industries, from synthetic leather to flooring, emphasizing its diverse applications. Sustainable Development: Understanding PVC's role in industrial contexts highlights opportunities for sustainable development and innovation, contributing to environmental conservation efforts. Qualitative Approach: Utilizing interviews, observations, and literature review, the research offers in-depth insights into the utilization of PVC in East Java, Indonesia. Keywords: PVC, applications, East Java, Indonesia, qualitative research